Pembuatan Bio-Produk Eco Enzyme Ramah Lingkungan Hasil Daur Ulang Limbah Organik sebagai Penunjang Pembelajaran Biologi - Naimnule, Lusia; Halek, Erlin Fatima; Atini, Blasius; Naimnule, Maria; Agu, Yakobus P.E.S.; Neonbeni, Eduardus Y. (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This article describes the results of community service activities aimed at students of Dharma Ayu Kefamenanu High School, with the aim that students are able to address waste problems in the school environment. There are two alternatives that can be used to solve the problem of organic waste, namely first throwing the waste in its place, and second processing the waste into a more beneficial product. This community service activity is more focused on the second alternative, namely that students are trained to be able to recycle organic waste into useful products. One of the bio-products is ecoenzyme, where this product uses organic solid waste and names the obtained solution as waste enzyme. Ecoenzyme products are also very functional and relatively easy to make as they use simple and accessible ingredients. This community service activity uses socialization methods and direct training for students related to the management of organic waste into ecoenzyme bio-products. This research method is applied through several stages including the observation stage, implementation stage, and follow-up stage. The result of this service activity is that students can understand the utilization of organic waste into more beneficial products, and the study related to this ecoenzyme product can be integrated into the learning process because it can train teachers and students to develop creativity in expressing new ideas for the development of learning innovations.